Reflective Study of Teachers' Strategies for Managing Art and Culture Classes in the Last Hour of Learning - Nidaus Sa’diyah; Taufik; Galuh Jevani Pambawati; Nur Romdlon Maslahul Adi (Journal of Practice Learning and Educational Development, 2026)
This study explores teachers' strategies for managing Arts and Culture learning during the final session at Al-Chusnaini Islamic Elementary School, a full-day Islamic elementary school. Ideally, Arts and Culture learning is expected to foster creativity, artistic expression, and active student engagement. However, in reality, students often experience fatigue and decreased concentration during the final session, resulting in suboptimal learning. This problem requires teachers to design creative and varied classroom management strategies to maintain student motivation and participation. This study uses a qualitative descriptive approach, with data obtained through observation, documentation, and teaching reflection. The results showed that teachers implemented several strategies, including educational games such as modified Monopoly, interactive digital media, icebreaker activities, group projects, and simple rewards. These strategies were effective in increasing student engagement, maintaining focus, and creating a fun and interactive learning atmosphere. This study highlights the importance of innovative classroom management to maintain student motivation and learning quality, especially during low-energy periods, where the implementation of game-based learning and cooperative models such as Teams Games Tournament (TGT) proved practical and had a positive impact. These findings are expected to contribute to the development of learning strategies for end-of-day sessions in elementary schools